Effect of pulsed electric field pretreatment synergistic mixed bacterial agent fermentation on the flavor and quality of air-dried goose meat and its molecular mechanism - Yujing Zhou; Jue Xu; Xiankang Fan; Qiang Xia; Changyu Zhou; Yangyang Hu; Hongbing Yan; Yangying Sun; Daodong Pan (Poultry Science)
In this study, the effect of pulsed electric field (PEF) pretreatment synergistic mixed bacterial agent (Lactiplantibacillus plantarum PDD-1 and Lactococcus lactis subsp. lactis JCM5805) fermentation on the flavor and quality of air-dried goose meat and its molecular mechanism were investigated. The results showed that PEF combined with the mixed bacteria fermentation increased activity of monoamine oxidase (232.57 U/mg protein), decreased TBARS (0.3 mg/kg) and TVB-N (15.75 mg/100 g) content, and the hardness and chewiness in air-dried goose. The improvement in flavor due to the synergistic fermentation following PEF pretreatment was primarily attributed to increased levels of aromatic compounds such as Heptanal (green, sweet), (Z)-3-Hexenyl acetate (green fruity), 3-(methylthio)-propanol (onion, bouillion-like note), alongside decreased levels of off-flavor compounds like methyl phenylacetate and 5-methyl-2-acetylfuran, as determined by the e-nose and GC-IMS. Colony counts and high-throughput sequencing demonstrated that Lactococcus and Staphylococcus predominated as the primary bacterial species, with different bioma onion, bouillion-like note rkers present in different air-dried goose groups. This is of strategic importance to develop the unique flavor and quality guarantee of air-dried goose.